Sweat sensor and preparation method and application thereof

By combining enzymes with copper ions into organic and inorganic hybrid nanoflower structures, and combining flexible substrate design, the problems of insufficient enzyme inactivity, environmental interference and long-term stability in sweat analysis by traditional enzyme-based biosensors are solved, and high sensitivity detection and real-time monitoring of Parkinson's disease-related biomarkers are achieved.

CN119881034AActive Publication Date: 2025-04-25CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510076492.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Existing traditional enzyme-based biosensors face problems such as enzyme inactivity, environmental interference and long-term stability in sweat analysis, and it is difficult to meet the needs of real-time and dynamic monitoring.

Method used

Biomineralization method is used to combine enzymes with copper ions into organic inorganic hybrid nanoflower structures, and combined with flexible substrate design, a sweat sensor based on organic inorganic hybrid nanoflower was developed.

Benefits of technology

The catalytic activity and stability of the enzyme are improved through the nanoflower structure, and high sensitivity detection of Parkinson's disease-related biomarkers is achieved, which improves the flexibility and portability of the sensor, and is suitable for real-time and continuous sweat monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119881034A_ABST
    Figure CN119881034A_ABST
Patent Text Reader

Abstract

The invention discloses a sweat sensor as well as a preparation method and application thereof, relates to the technical field of biosensors, and solves the problems of blank of hybrid nanoflowers in the field of sweat analysis and limited long-term stability of traditional biosensors. The enzyme solution and the copper sulfate solution are mixed and oscillated uniformly, and a mineralization reaction of enzyme molecules is carried out in a water bath to obtain purified enzyme nanoflowers; designing a multi-electrode array, and printing conductive silver paste on a PET substrate to form an electrode wire and a silver electrode; printing three working electrodes and a counter electrode by adopting conductive carbon ink; forming a reference electrode on the surface of the silver electrode; printing insulating ink as a circuit protection layer; after electrode activation, dispersing the multi-walled carbon nanotubes in DMF, and after coating, forming a PB / PPy film on the surface of the electrode through electropolymerization; dropwise adding the enzyme nanoflower solution to the surface of a working electrode, and coating a chitosan protective film to obtain the sensor. The method has a wide application prospect and an important social value in the fields of medical detection and health monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biosensors, and in particular to a sweat sensor and a preparation method and application thereof. Background Art

[0002] As an important body fluid, human sweat contains rich biological information, and its composition is closely related to health status and physiological metabolism. In recent years, sweat analysis has attracted widespread attention due to its non-invasive, real-time and continuous monitoring characteristics, and has become an important research direction in the field of flexible electronics. By detecting metabolites (such as glucose, uric acid, lactic acid, amino acids, etc.) and electrolytes (such as sodium ions, potassium ions, chloride ions, etc.) in sweat, the body's exercise status, nutritional status and potential disease risks can be evaluated. In particular, the detection of markers related to neurodegenerative diseases in sweat, such as levodopa, ascorbic acid and glucose, is of great significance for the early diagnosis of diseases such as Parkinson's disease.

[0003] Biosensors have been widely used in biomarker detection due to their high sensitivity and specificity. Traditional enzyme-based biosensors occupy an important position in the field of biosensors and are one of the earliest developed and most widely used types of biosensors. Enzyme-based biosensors utilize the high specificity and catalytic efficiency of enzymes to convert specific biochemical reactions into easily measurable electrical signals or other forms of signals, thereby achieving rapid and accurate detection of specific substances. However, traditional enzyme-based biosensors still face multiple challenges in practical applications, including: (1) the inactivation of enzymes. Enzymes are easily inactivated under conditions of high temperature, humidity changes, and long-term use, which significantly reduces the reliability and service life of sensors; (2) the influence of environmental interference. Sweat has a complex composition and is easily interfered by factors such as pH value and ionic strength, resulting in a decrease in the accuracy of detection results; (3) the lack of long-term stability of sensors. Existing sensors are prone to performance degradation under continuous monitoring conditions and are difficult to meet the needs of real-time and dynamic monitoring. Therefore, improving the catalytic activity and stability of enzymes has become an important research direction in the field of biosensors.

[0004] In recent years, researchers have tried to improve the stability of enzymes by coating them with metal-organic framework (MOF) structures. However, while this method enhances stability, it inevitably leads to a decrease in the catalytic activity of the enzyme, limiting its practical application. Therefore, developing an innovative strategy that can take into account both the catalytic activity and stability of the enzyme remains a key issue that needs to be addressed in this field.

[0005] By combining organic materials (such as enzyme molecules) with inorganic materials (such as metal ions), the activity and stability of the enzyme can be significantly improved, while the selectivity and anti-interference ability of the sensor for the target substance can be enhanced. Hybrid nanoflowers have the following advantages: (1) High specific surface area: It is conducive to the fixation of enzyme molecules and the adsorption of target substances, improving detection sensitivity; (2) Enhanced catalytic performance: The inorganic components provide a stable microenvironment for enzyme molecules, significantly improving catalytic efficiency; (3) Excellent structural stability: The nanoflower structure can effectively protect the enzyme from the influence of external environmental factors and improve long-term stability. However, although hybrid nanoflowers have shown great potential under laboratory conditions, their practical application in the field of sweat analysis is still in its early stages, especially for real-time monitoring equipment for Parkinson's disease-related markers. In addition, the design of traditional flexible sensors is usually difficult to balance flexibility, stability and high sensitivity. Moreover, existing sensors mostly rely on complex structural designs and expensive materials, and the preparation process is cumbersome and costly, which is difficult to meet the needs of large-scale commercialization. Summary of the invention

[0006] In order to solve the application gap of existing hybrid nanoflowers in the field of sweat analysis and the problem of limited long-term stability of traditional biosensors, the present invention proposes a sweat sensor based on organic-inorganic hybrid nanoflowers and its preparation method and application.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a sweat sensor comprises the following steps:

[0009] S1. Dissolve the enzyme in a phosphate buffer solution to obtain an enzyme solution, then add a copper sulfate solution and oscillate evenly; incubate the mixed solution in a water bath to allow the mineralization reaction of the enzyme molecules to occur, collect the precipitate by centrifugation, and wash with ultrapure water to remove the unreacted enzyme to obtain purified enzyme nanoflowers;

[0010] S2, design a multi-electrode array and outsource the production of a mask plate, which is fixed on a PET substrate;

[0011] Printing and coating conductive silver paste to form electrode wires and a silver electrode, and baking and curing;

[0012] Three working electrodes and one counter electrode were printed using conductive carbon ink;

[0013] Add FeCl3 solution on the surface of the silver electrode to form an Ag / AgCl reference electrode;

[0014] Printing insulating ink as a circuit protection layer, curing under UV light;

[0015] S3, performing electrode activation by cyclic voltammetry, and then dispersing the multi-walled carbon nanotubes in a DMF solution, coating the surface of the carbon working electrode and drying;

[0016] Pyrrole and Prussian blue were simultaneously polymerized on the surface of the working electrode to form a PB / PPy composite film;

[0017] The enzyme nanoflower solution obtained in step S1 was added dropwise to the surface of the PB / PPy-modified working electrode and dried at room temperature overnight;

[0018] Chitosan solution is drop-coated on the surface of the working electrode and dried naturally to form a stable protective film to obtain a sweat sensor.

[0019] Preferably, in step S1, the concentration of the phosphate buffer solution is 0.01 mol / L, and the pH is 7.4; the concentration of the copper sulfate solution is 60 mmol / L to 150 mmol / L;

[0020] Specifically, the concentration of the copper sulfate solution can be 60mmol / L, 80mmol / L, 100mmol / L, 120mmol / L, 150mmol / L, and most preferably 120mmol / L;

[0021] The concentration of the enzyme solution is 0.1 mg / mL to 1 mg / mL.

[0022] Preferably, the enzyme in step S1 is one of glucose oxidase, ascorbic acid oxidase and tyrosinase; the concentration of the glucose oxidase solution is preferably 0.5 mg / mL, the concentration of the ascorbic acid oxidase solution is preferably 1 mg / mL, and the concentration of the tyrosinase solution is preferably 0.72 mg / mL.

[0023] Preferably, in step S1, the water bath temperature is 25° C., the incubation time is 72 h; the centrifugal speed is 3500 rpm, the centrifugal time is 10 min; and the washing times are 3 times.

[0024] Preferably, in step S2, the thickness of the PET substrate is 0.1 mm; the size of the mask is 10 cm*10 cm, and the thickness is 125 μm.

[0025] Preferably, the resistivity of the conductive carbon ink in step S2 is 10Ω / cm 2 .

[0026] Preferably, the baking and curing temperature in step S2 is 60° C., and the baking and curing time is 30 minutes.

[0027] Preferably, the concentration of the FeCl3 solution in step S2 is 0.05 mol / L, and the amount of addition is 5 mL.

[0028] Preferably, in step S3, the amount of the enzyme nanoflower solution added is 5 μL, and the amount of the chitosan solution added is 4 μL.

[0029] The present invention also provides a sweat sensor, which is prepared by using the above preparation method.

[0030] The present invention also provides an application of the sweat sensor in a real-time monitoring device for Parkinson's disease related markers.

[0031] Compared with the prior art, the specific beneficial effects of the present invention are:

[0032] Based on the biomineralization method, this scheme prepares copper ions, glucose oxidase, ascorbic acid oxidase and tyrosinase into organic-inorganic hybrid nanoflower structures, and combines them with flexible substrate design to develop a flexible wearable sweat sensor. The unique biomineralization properties of nanoflowers and the efficient catalytic properties of organic enzymes combined with the stability of inorganic materials are used to detect Parkinson's disease-related biomarkers.

[0033] 1. High sensitivity and improved stability:

[0034] The structure of organic-inorganic hybrid nanoflowers significantly improves the catalytic activity of enzymes. This nanoflower structure provides enzymes with a larger specific surface area and a more suitable microenvironment, promoting the contact and reaction between enzymes and substrates, thereby enhancing the catalytic efficiency of Parkinson's disease-related biomarkers (such as levodopa, ascorbic acid and glucose) and achieving efficient detection.

[0035] The nanoflower structure effectively improves the stability of the enzyme. Traditional enzymes are easily inactivated in the external environment, while the nanoflower structure can protect the active center of the enzyme, allowing it to maintain high activity for a long time. For example, in practical applications, even after a long period of use or in a complex physiological environment, the sensor can still function stably, ensuring the accuracy and reliability of the test results.

[0036] 2. Flexibility and portability:

[0037] The sensor base is made of flexible PET material, which has good flexibility and mechanical adaptability. It can fit human skin well, especially when the human body is moving, and the performance and wearing comfort of the sensor will not be affected by the bending and stretching of the body.

[0038] Due to its flexibility and lightness, the sensor can be easily integrated into wearable devices such as clothing and bracelets for long-term wear. Users will hardly feel the presence of the sensor in their daily lives, which will not interfere with their normal lives. It is very suitable for real-time and continuous sweat monitoring.

[0039] 3. Multi-marker monitoring:

[0040] The sensor provided by the present invention can simultaneously monitor multiple Parkinson's disease-related biomarkers, such as levodopa, ascorbic acid and glucose, etc. These markers play an important indicative role in the occurrence and development of Parkinson's disease. By detecting them simultaneously, we can have a more comprehensive understanding of the physiological state of the human body and provide more abundant information for the early diagnosis of the disease.

[0041] 4. The preparation process of the present invention is relatively simple, does not require complex equipment and harsh reaction conditions, reduces energy consumption and the use of chemical reagents, and is environmentally friendly. In addition, the materials used are low in cost and widely available, which is conducive to large-scale production and commercial promotion.

[0042] The present invention provides a new idea for the design and development of wearable biosensors, and has broad application prospects and important social value in the fields of medical detection and health monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a microscopic morphology of the enzyme nanoflower prepared in Example 1;

[0044] Figure 2 This is the elemental analysis result diagram of the glucose oxidase nanoflowers prepared in Example 1;

[0045] Figure 3 The results of the long-term stability comparison between three nanoflowers (GOx-NFs, AOx-NFs, Tyr-NFs) and pure enzymes are shown in the figure;

[0046] Figure 4 Schematic diagram of the preparation process of screen-printed electrodes;

[0047] Figure 5 A schematic diagram of the structure of the biosensor provided by the present invention;

[0048] Figure 6 The electrochemical detection results of the biosensor provided by the present invention;

[0049] Figure 7 The surface test results of the biosensor provided by the present invention;

[0050] Figure 8 This is a schematic diagram of the detection principle of the biosensor provided by the present invention. DETAILED DESCRIPTION

[0051] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0052] Example 1.

[0053] In this example, glucose oxidase nanoflowers were prepared by the following steps:

[0054] S1. Preparation and reaction of CuSO solution and enzyme solution:

[0055] (1) Weigh 29.9 mg of copper sulfate pentahydrate powder and add it to 1 mL of ultrapure water. Dissolve it under ultrasonication to form a clear blue solution, which is marked as 120 mmol / L CuSO solution.

[0056] (2) Add 0.555 mL of 0.01 mol / L, pH 7.4 phosphate buffer solution to 10 KU, ≥ 180 U / mg glucose oxidase, shake well, and mark as 100 mg / mL glucose oxidase solution. Take 5 μL of the above glucose oxidase solution and add it to 995 μL of 0.01 mol / L, pH 7.4 phosphate buffer solution, shake well, and mark as 0.5 mg / mL glucose oxidase solution.

[0057] (3) Take 20 μL of the above CuSOD solution and add it to 1 mL of 0.5 mg / mL glucose oxidase solution. Mix well and place in a 25°C water bath for 72 h.

[0058] S2. After the reaction, the precipitate was separated by centrifugation (3500 rpm, 10 min) and washed three times with ultrapure water to remove unbound enzyme and salt ions to obtain purified glucose oxidase nanoflower GO. x -NFs.

[0059] The microscopic morphology of the enzyme nanoflower was scanned, and its microscopic morphology is as follows Figure 1 The elemental analysis of the enzyme nanoflower is shown in Figure 2 , further proving that the enzyme nanoflower is composed of a copper phosphate skeleton and the glucose oxidase therein.

[0060] Example 2.

[0061] In this example, ascorbate oxidase nanoflowers were prepared by the following steps:

[0062] S1. Preparation and reaction of CuSO solution and enzyme solution:

[0063] (1) Weigh 29.9 mg of copper sulfate pentahydrate powder and add it to 1 mL of ultrapure water. Dissolve it under ultrasonication to form a clear blue solution, which is marked as 120 mmol / L CuSO solution.

[0064] (2) Add 0.555 mL of 0.01 mol / L, pH 7.4 phosphate buffer solution to 10 KU, ≥180 U / mg ascorbate oxidase, shake well, and label it as 100 mg / mL glucose oxidase solution. Then take 10 μL of the above ascorbate oxidase solution and add it to 990 μL of 0.01 mol / L, pH 7.4 phosphate buffer solution, shake well, and label it as 1 mg / mL ascorbate oxidase.

[0065] (3) Take 20 μL of the above CuSO solution and add it to 1 mL of 0.5 mg / mL ascorbic acid oxidase solution. Mix well and place in a 25°C water bath for 72 h.

[0066] S2. After the reaction is completed, the precipitate is separated by centrifugation (3500 rpm, 10 min), and washed three times with ultrapure water to remove unbound enzymes and salt ions to obtain purified ascorbic acid oxidase nanoflowers AOx-NFs.

[0067] Example 3.

[0068] In this example, ascorbate oxidase nanoflowers were prepared by the following steps:

[0069] S1. Preparation and reaction of CuSO solution and enzyme solution:

[0070] (1) Weigh 29.9 mg of copper sulfate pentahydrate powder and add it to 1 mL of ultrapure water. Dissolve it under ultrasonication to form a clear blue solution, which is marked as 120 mmol / L CuSO solution.

[0071] (2) Add 0.555 mL of 0.01 mol / L, pH 7.4 phosphate buffer solution to 10 KU, ≥180 U / mg tyrosinase, shake well, and mark as 100 mg / mL tyrosinase solution. Then take 7.2 μL of the above tyrosinase solution and add it to 992.8 μL of 0.01 mol / L, pH 7.4 phosphate buffer solution, shake well, and mark as 0.72 mg / mL tyrosinase solution.

[0072] (3) Take 20 μL of the above CuSO solution and add it to 1 mL of 0.5 mg / mL tyrosinase solution. Mix well and place in a 25°C water bath for 72 h.

[0073] S2. After the reaction is completed, the precipitate is separated by centrifugation (3500 rpm, 10 min), and washed three times with ultrapure water to remove unbound enzymes and salt ions to obtain purified tyrosinase nanoflowers Tyr-NFs.

[0074] Example 4.

[0075] This example tests the catalytic activity of the enzyme nanoflowers prepared in Examples 1 to 3:

[0076] S1, GO x and GO x -NFs catalytic activity test:

[0077] (1) 20 μL GO x -NFs and GO x The solution (0.5 mg / mL) was added to 400 μL PBS (pH=7.4, 0.01 mol / L), followed by the addition of 600 μL 1-10 mmol / L glucose solution.

[0078] (2) After incubation at 35°C for 20 min, 100 μL TMB (20 mmol / L) and 20 μL HRP (0.1 mg / mL) were added.

[0079] The absorbance was measured at 370 nm using a UV-visible spectrometer.

[0080] Comparison of free GO x and GO x Relative activity of NFs to free GO x The activity was taken as 100% for reference.

[0081] S2、AO x and AO x -NFs catalytic activity test:

[0082] (1) 70 μL of ascorbic acid (1-10 mmol / L), 150 μL of phen and 150 μL of NH4Fe(SO4)2·12H2O were added to 2150 μL of sodium acetate buffer (pH=5.6, 0.1 M), incubated at 35°C for 10 min, and then the absorbance at 450 nm was measured using a UV-visible spectrometer.

[0083] (2) Add 20 μL of AO to 70 μL of ascorbic acid (1-10 mmol / L) solution. x -NFs and AO x Solution (1 mg / mL), incubate for 10 min, then repeat (1).

[0084] (3) Calculate the difference in absorbance at 450 nm.

[0085] (4) Free AO x Activity was used as a reference to evaluate the immobilized AO x -Activity of NFs.

[0086] S3, Tyr and Tyr-NFs activity test:

[0087] (1) Add 100 μL L-Dopa (1-5 mmol / L) and 100 μL Tyr-NFs (0.72 mg / mL) to 300 μL PBS (pH=7.4, 0.01 M) and incubate at 35°C for 20 min.

[0088] (2) The absorbance was measured at 475 nm using a UV-visible absorption spectrometer.

[0089] (3) The relative activities of free Tyr and Tyr-NFs were compared, with the free Tyr activity being taken as 100% for reference.

[0090] Figure 3 For three nanoflowers (GO x -NFs、AO x Schematic diagram of the long-term stability test results of the three pure enzymes (GO-NFs, Tyr-NFs) and pure enzymes. x , AO x , Tyr) performed poorly in terms of long-term stability. As time went by, their relative activities decreased to varying degrees. Among them, Tyr had the worst stability and its enzyme activity was almost completely lost in a short period of time. x -NFs、AO x -NFs, Tyr-NFs), the stability was significantly improved. Within 60 days, the relative activity of enzyme nanoflowers was able to maintain a high level, especially GO x -NFs and AO x -NFs, there was almost no significant decrease in relative activity.

[0091] All the above tests were performed three times in parallel to ensure the reliability of the data.

[0092] Example 5.

[0093] In this embodiment, the screen-printed electrode is prepared by the following steps. The schematic diagram of the preparation process is shown in FIG. Figure 4 shown.

[0094] S1. Electrode design and template preparation:

[0095] AutoCAD 2021 was used to design a multi-electrode array, including three working electrodes (WE), a counter electrode (CE) and a reference electrode (RE). The array was outsourced to produce a 125 μm thick 10 cm*10 cm mask plate and fixed on a PET substrate (thickness 0.1 mm) using a semi-automatic screen printer.

[0096] S2, Silver ink printing:

[0097] Use an oily polyurethane scraper to print a layer of conductive silver paste on the substrate at a speed of 5 cm per second to form a conductive circuit and the initial shape of the electrode. The printed substrate is baked at 60°C for 30 minutes to solidify the silver ink.

[0098] S3, Carbon ink printing:

[0099] Conductive carbon ink and acetone were mixed evenly in a volume ratio of 20:1, and then the conductive carbon ink (resistivity 10Ωcm-2) was screen-printed at a speed of 5 cm per second using an oily polyurethane scraper to prepare three working electrodes and a counter electrode, and baked at 60°C for 30 min.

[0100] S4. Reference electrode preparation:

[0101] 5 mL of FeCl solution (0.05 mol / L) was drop-coated on the silver electrode, and after reacting for 1 min, it was rinsed with ultrapure water and dried for 30 min to prepare the Ag / AgCl reference electrode.

[0102] S5. Protective layer printing:

[0103] An oily polyurethane squeegee was used to screen print insulating ink at a speed of 5 cm per second to cover the wire area connecting the working electrode to the interface, and then cured under 365 nm ultraviolet light for 2 h.

[0104] S6. Conductivity verification:

[0105] Use a multimeter to test the resistance between the electrode and the interface of each conductive path to ensure the integrity and conductivity of the electrode.

[0106] Example 6.

[0107] In this embodiment, the sensor was assembled and modified according to the following steps:

[0108] S1. Electrode activation:

[0109] One end of the screen-printed electrode was connected to the electrochemical workstation through an interface, and the working electrode, reference electrode and counter electrode at one end were immersed in 0.5 mol / L HSO solution. The electrode was activated by cyclic voltammetry on the electrochemical workstation with a potential range of -1.0 V to 1.5 V, a scan rate of 50 mV / s, and 30 cycles.

[0110] S2, MWCNT coating:

[0111] 10 mg of MWCNT was dispersed in 1 mL of DMF solution, and after ultrasonic dispersion for 1 h, 4 μL was drop-coated on the surface of each carbon working electrode, and then placed on a 35°C hot stage for drying for 30 min.

[0112] S3, PB / PPy membrane electropolymerization:

[0113] Pyrrole (0.08 mol / L), KFe(CN) (2.5 mmol / L), FeCl (2.5 mmol / L) and HCl (0.1 mmol / L) were added to 5 mL of ultrapure water and stirred for 5 min. The electrode was connected to an electrochemical workstation and CV was used to scan 20 times in the potential range of -0.2 V to 0.9 V to prepare a PB / PPy composite film, and then the electrode surface was rinsed with ultrapure water for 3 times.

[0114] S4, Nanoflower Modification:

[0115] 5 μL of GO prepared in Examples 1 to 3 was drop-coated on the PB / PPy modified working electrodes. x -NFs、AO x -NFs and Tyr-NFs solutions were left at room temperature overnight and dried naturally.

[0116] S5, Chitosan protective film:

[0117] 0.05g chitosan powder was added to a clean beaker, and 50mL 0.1mol / L acetic acid solution was added. Ultrasonication was performed for 5min, and then magnetic stirring was performed for 2h to obtain a clear and transparent solution. 4μL of the chitosan solution was dropped onto the working electrode and dried at room temperature to form a protective film. The obtained sensor structure is shown in FIG. Figure 5 shown.

[0118] Example 7.

[0119] This example tests the performance of the sensor obtained in Example 6:

[0120] S1. Calibration of biomarker concentration curve:

[0121] (1) Use 0.01 mol / L phosphate buffer solution with a pH of 7.4 to prepare 1-100 μmol / L levodopa solution, 1-500 μmol / L glucose solution and ascorbic acid solution.

[0122] (2) The chronoamperometry method was used to test the response of the sensor to the gradually changing concentrations of L-DOPA, glucose and ascorbic acid. Different concentrations of the target substances were gradually added to the phosphate buffer, and a standard curve of current density and concentration was drawn. The test results were as follows: Figure 6 As shown in the figure, the overall electrochemical detection results show that the biosensor based on the three enzyme nanoflowers has a good response to the three Parkinson's disease related markers, namely glucose, ascorbic acid and levodopa, and within a certain concentration range, there is a good linear relationship between the marker concentration and the current, which can achieve quantitative detection of these markers and provide valuable technical support for the diagnosis and monitoring of Parkinson's disease.

[0123] S2. Surface experiment:

[0124] The sensor was attached to the skin of volunteers, and sweating was induced by spinning under constant exercise load. The concentration changes of markers in sweat during exercise were monitored in real time. The test results were as follows: Figure 7 As shown. The test process is divided into three stages, marked as I, II, and III. In the first stage, since the volunteers have not sweated yet, the sensor has no obvious signal. When the volunteers began to sweat and came into contact with the sensor surface, a strong signal change occurred instantly. Then, due to the stability of the amount of sweat, the diffusion of the detection substance in the sweat on the electrode surface also tended to be stable, and a stable and accurate test result was obtained at this time. Then the test ended, and after the sensor was removed, the current signal disappeared. The test results can prove that the sensor can detect glucose, ascorbic acid and levodopa in sweat in real time during the body surface test, and has an obvious current response to the concentration changes of these three substances. It can sensitively detect the dynamic changes in the concentration of these substances in sweat during sweating, indicating that the sensor has the ability to be used for the detection of related substances in the actual body surface environment, which provides the possibility for real-time monitoring of Parkinson's disease and other related diseases.

[0125] Figure 8Schematic diagram of the working principle of the sensor provided by the present invention. The blue part in the figure is an enzyme nanoflower structure. Since this structure has a large specific surface area, it can load a large amount of enzymes, and by introducing additional metal ions and enzymes to form a synergistic catalytic effect, the catalytic efficiency and the stability of the sensing core can be improved. When the sample solution containing the substrate contacts the sensor loaded with the enzyme nanoflower, the substrate molecules will diffuse to the surface of the enzyme nanoflower, and the enzyme will specifically recognize and catalyze the substrate to react. In this process, electrons will be transferred between the enzyme and the substrate. The electrons generated by the enzyme catalytic reaction are transferred to the working electrode through the nanoflower structure to form a redox current, and the magnitude of the current is directly related to the concentration of the analyte. By measuring the change of the response current on the working electrode over time by the chronoamperometry (as shown in the curve graph on the right), a current signal can be obtained. When the substrate concentration is high, the redox current generated is large; conversely, when the substrate concentration is low, the redox current is small. By analyzing and calibrating the response current, a quantitative relationship between the substrate concentration and the current change (ΔI) can be established, thereby realizing the detection and quantitative analysis of the substrate.

Claims

1. A method for preparing a sweat sensor, characterized in that: The steps include: S1. Dissolve the enzyme in a phosphate buffer solution to obtain an enzyme solution, then add a copper sulfate solution and oscillate evenly; incubate the mixed solution in a water bath to allow the mineralization reaction of the enzyme molecules to occur, collect the precipitate by centrifugation, and wash with ultrapure water to remove the unreacted enzyme to obtain purified enzyme nanoflowers; S2, design a multi-electrode array and outsource the production of a mask plate, which is fixed on a PET substrate; Printing and coating conductive silver paste to form electrode wires and a silver electrode, and baking and curing; Three working electrodes and one counter electrode were printed using conductive carbon ink; Add FeCl3 solution on the surface of the silver electrode to form an Ag / AgCl reference electrode; Printing insulating ink as a circuit protection layer, curing under UV light; S3, performing electrode activation by cyclic voltammetry, and then dispersing the multi-walled carbon nanotubes in a DMF solution, coating the surface of the carbon working electrode and drying; Pyrrole and Prussian blue were simultaneously polymerized on the surface of the working electrode to form a PB / PPy composite film; The enzyme nanoflower solution obtained in step S1 was added dropwise to the surface of the working electrode modified with the PB / PPy composite film and dried at room temperature overnight; Chitosan solution is drop-coated on the surface of the working electrode and dried naturally to form a stable protective film to obtain a sweat sensor.

2. The method for preparing a sweat sensor according to claim 2, characterized in that: In step S1, the concentration of the phosphate buffer solution is 0.01 mol / L, and the pH is 7.4; the concentration of the copper sulfate solution is 60 mmol / L to 150 mmol / L; and the concentration of the enzyme solution is 0.1 mg / mL to 1 mg / mL.

3. The method for preparing a sweat sensor according to claim 1, characterized in that: In step S1, the enzyme is one of glucose oxidase, ascorbic acid oxidase and tyrosinase; the concentration of the glucose oxidase solution is 0.5 mg / mL, the concentration of the ascorbic acid oxidase solution is 1 mg / mL, and the concentration of the tyrosinase solution is 0.72 mg / mL.

4. The method for preparing a sweat sensor according to claim 1, characterized in that: In step S1, the water bath temperature is 25° C., the incubation time is 72 h; the centrifugal speed is 3500 rpm, the centrifugal time is 10 min; and the washing times are 3 times.

5. The method for preparing a sweat sensor according to claim 1, characterized in that: In step S2, the thickness of the PET substrate is 0.1 mm; the size of the mask is 10 cm*10 cm, and the thickness is 125 μm.

6. The method for preparing a sweat sensor according to claim 1, characterized in that: The resistivity of the conductive carbon ink in step S2 is 10Ω / cm 2 .

7. The method for preparing a sweat sensor according to claim 1, characterized in that: The concentration of the FeCl3 solution in step S2 is 0.05 mol / L, and the amount added is 5 mL.

8. The method for preparing a sweat sensor according to claim 1, characterized in that: In step S3, the amount of the enzyme nanoflower solution added is 5 μL, and the amount of the chitosan solution added is 4 μL.

9. A sweat sensor, characterized in that: The method is used to prepare the product according to any one of claims 1 to 8.

10. Use of the sweat sensor according to claim 9 in a wearable device for real-time monitoring of Parkinson's disease-related markers.

Citation Information

Patent Citations

  • Flexible sweat and sugar electrochemical sensor

    CN114487064A

  • Photoelectrochemical enzyme sensor for ascorbic acid detection as well as preparation method and application of photoelectrochemical enzyme sensor

    CN115032249A

  • Flexible glucose sensor and preparation method thereof

    CN115656287A

  • Preparation and application of intelligent double-response nanoflower material

    CN116785452A

  • Multi-parameter flexible / wearable sweat sensor and preparation method thereof

    CN117405751A

Cited By

  • Sweat multi-parameter ion detection sensor, system and method

    CN121090637A